Women's images in Turkish cinema in the context of orientalism: The samples of Tight Dress - Tanyildizi, Nural Imik; Yolcu, Ayşe Şebnem (IGI Global, 2021)
Orientalism, which we can define as how the West recognizes the East, can be determined in many different fields such as literature, music, and architectural painting since ancient times. In orientalist ideology, the negative traits of the other are always emphasized. Because, as Said also emphasizes, the West can only create its own self by alienating and negating the East. The representation styles of marginalized societies; identities and genders are negative in parallel with the Western understanding in the movies that are dominated by the orientalist ideology. The Eastern woman, who is currently the absolute other in terms of gender, is marginalized once again in the examples of Orientalist cinema. This study, based on the movie Tight Dress, aims to observe the hegemonic structure of the willingness to represent women in the patriarchal order of the Eastern Muslim-Turkish representation of women produced within the Western masculine fantasy discourse within the framework of feminist theory and to reveal the orientalist elements in the film through semiotic analysis. © 2021, IGI Global.